Jejak Industri Ekstraktif: Analisis Kerusakan Hutan, Konflik Agraria, Dan Dugaan Pelanggaran Oleh PT. Toba Pulp Lestari, Tbk - Rina Widiyanti Silalahi; Jeny Azinta; Salsabila Putri I. Simbolon; Miftahul Choir Sinaga; Reihan Carlo Sipayung; Kristine Manasye Simanjuntak; Dian G Purba (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the impact of PT. Toba Pulp Lestari Tbk's extractive industry activities on the environment, society, and natural resource governance in Indonesia. The method used is a qualitative case study approach through descriptive analysis of secondary data derived from company reports, government documents, scientific journals, and related literature. The results indicate that industrial forest plantation (HTI) management and pulp production contribute to the economy through job creation, increased industrial activity, and meeting the need for paper raw materials. However, these activities also pose various challenges, such as ecosystem changes due to eucalyptus monoculture, potential biodiversity decline, agrarian conflicts with local and indigenous communities, and criticism of transparency and corporate governance. These conditions reflect the tension between economic interests and environmental sustainability and social justice. Therefore, strengthening governance, increasing transparency, effective government oversight, and implementing sustainable natural resource management are needed.